2021
DOI: 10.9734/ajeba/2021/v21i2230523
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Financial Performance on Prediction Financial Distress

Abstract: Aims: This study aims to empirically test ieffect of Current Ratio (CR), Debt to Equity Ratio (DER), Total Assets Turnover (TATO) and Return on Assets (ROA) on Financial Distress using the Altman Z-Score method. This analysis uses independent variables, there are CR, DER, TATO and ROA with dependent variable is Financial Distress (FD). Study Design: Design study is quantitative research and using statistical analysis. Place and duration of Study: The research population and sample used is a public … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…Sinyal ini berupa informasi mengenai keberhasilan dan kegagalan manajemen dalam menjalankan kinerja perusahaan. Hal ini adalah sebuah petunjuk kepada investor mengenai manajemen perusahaan dalam memandang kemajuan dan tujuan perusahaan (Laksmiwati et al, 2021).…”
Section: Landasan Teori Dan Hipotesisunclassified
“…Sinyal ini berupa informasi mengenai keberhasilan dan kegagalan manajemen dalam menjalankan kinerja perusahaan. Hal ini adalah sebuah petunjuk kepada investor mengenai manajemen perusahaan dalam memandang kemajuan dan tujuan perusahaan (Laksmiwati et al, 2021).…”
Section: Landasan Teori Dan Hipotesisunclassified
“…High profitability shows that the company can generate profits that can be used to fund the company's operations or pay its obligations so as to make the company survive and avoid the threat of financial distress (Carolina et al, 2018;Indriaty et al, 2019). However, the results of research conducted by Destriwanti et al, (2022) and Laksmiwati et al, (2021) provide different results, where the level of profitability ratio will be followed by an increasing threat of companies experiencing financial distress. The two research results that showed differences in the influence of profitability were also contrary to research conducted by Setyobudi et al, (2017), which found that the level of profitability ratios had no influence on the possibility of financial distress.…”
Section: Introductionmentioning
confidence: 98%
“…A good level of liquidity indicates that the company has a good ability to meet its short-term obligations at maturity (Kasmir, 2008). Conversely, when the company has a low liquidity ratio, it means that the company's finances are in a bad state and are said to be in an illiquid position (Laksmiwati et al, 2021). A result study conducted by Hastiarto (2021) in manufacturing companies in Indonesia showed that companies would experience lower risks if they had a high percentage level of liquidity, this result is also in line with research by Mesak (2019) and Susdaryo et al, (2021) which showed that liquidity ratios have a significant negative influence on financial distress.…”
Section: Introductionmentioning
confidence: 99%